2003
DOI: 10.1353/csd.2003.0033
|View full text |Cite
|
Sign up to set email alerts
|

College Students and Learning Disability: Elements of Self-Style

Abstract: Students with learning disabilities are attending college at an increasing rate. Still, little is known about the phenomenon of experiencing a learning disability in postsecondary education. Through grounded theory methodology, this study explored the experiences of 9 college students with learning disabilities. The emergent theory points to elements of "self-style" as a means to operationally define learning disability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…A growing number of studies are employing grounded theory methodology as a means of understanding identity, in the context of the college environment (Jones, 1997;Jones & McEwen, 2000;Komives, Owen, Longerbeam, Mainella, & Osteen, 2005;Stevens, 2004;Torres, 2003;Troiano, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…A growing number of studies are employing grounded theory methodology as a means of understanding identity, in the context of the college environment (Jones, 1997;Jones & McEwen, 2000;Komives, Owen, Longerbeam, Mainella, & Osteen, 2005;Stevens, 2004;Torres, 2003;Troiano, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…The limited literature about the collegiate experiences of students with disabilities reveals conflicting findings about relationships with educators (Adams & Proctor, 2010;Ashby & Causton-Theoharis, 2012;Barnard-Brak, Lechtenberger, & Lan, 2010;Megivern, Pellerito, & Mowbray, 2003;Olney & Brockelman, 2003;Troiano, 2003). Two studies suggest that students with disabilities have difficulty developing positive relationships with, and/or obtaining necessary supports from faculty (Barnard-Brak et al, 2010;Olney & Brockelman, 2003), while another found almost exclusively positive relationships between faculty and students with disabilities (Troiano, 2003).…”
Section: Journal Of College Student Developmentmentioning
confidence: 99%
“…Two studies suggest that students with disabilities have difficulty developing positive relationships with, and/or obtaining necessary supports from faculty (Barnard-Brak et al, 2010;Olney & Brockelman, 2003), while another found almost exclusively positive relationships between faculty and students with disabilities (Troiano, 2003). Literature regarding peer relationships is less divided and less positive.…”
Section: Journal Of College Student Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…College counselors may also serve as consultants for faculty, staff, coaches, parents, community and student organizations from athletics to Greek organizations (Foubert & Newberry, 2006;Much, Wagener, & Hellenbrand, 2010) as well as advocates for underrepresented student populations (Zubernis & Snyder, 2007) and those managing disabilities (Corrigan, 1998;Troiano, 2003).…”
Section: Counselor Preparation Is Indispensable Counseling Services Amentioning
confidence: 99%